The Dyer-Roeder distance in quintessence cosmology and the estimation of H0 through time-delays - Giovi, Fabio; Occhionero, Franco; Amendola, Luca (Arxiv, 2000)
We calculate analytically and numerically the Dyer-Roeder distance in perfect fluid quintessence models and give an accurate fit to the numerical solutions for all the values of the density parameter and the quintessence equation of state. Then we apply our solutions to the estimation of $H_{0}$ from multiple image time delays and find that the inclusion of quintessence modifies sensibly the likelihood distribution of $H_{0}$, generally reducing the best estimate with respect to a pure cosmological constant. Marginalizing over the other parameters ($Ω_{m}$ and the quintessence equation of state), we obtain $H_{0}=71± 6$ km/sec/Mpc for an empty beam and $H_{0}=64± 4$ km/sec/Mpc for a filled beam. We also discuss the future prospects for distinguishing quintessence from a cosmological constant with time delays.